Tuning size and coverage of Pd nanoparticles using atomic layer deposition - Feng, Ji-Yu; Ramachandran, Ranjith K.; Solano, Eduardo; Minjauw, Matthias M.; Van Daele, Michiel; Vantomme, André; Hermida-Merino, Daniel; Coati, Alessandro; Poelman, Hilde; Detavernier, Christophe; Dendooven, Jolien (Applied surface science, 2021)
[Display omitted] •Synchrotron-based in situ GISAXS and XRF are applied during Pd plasma-enhanced ALD.•The nucleation and the evolution in Pd nanoparticle morphology is investigated.•Pre-pulses with trimethylaluminum enhance the initial coverage of Pd nanoparticles.•The role of extra O2 plasma pulse, with H2 plasma as co-reactant, is investigated.•Precise control of the Pd nanoparticle dimensions and coverage is achieved. The morphology evolution of supported palladium nanoparticles (Pd NPs) during plasma-enhanced atomic layer deposition using palladium hexafluoroacetylacetonate (Pd(hfac)2) as precursor was investigated using in situ and ex situ X-ray fluorescence (XRF) and grazing incidence small angle X-ray scattering (GISAXS), as well as ex situ scanning electron microscopy (SEM). The initial areal density of Pd NPs increases through adding cycles of the three-step process using Pd(hfac)2, H2 plasma and trimethylaluminum (TMA) prior to the standard Pd(hfac)2 + H2 plasma process. The participation of an O2 plasma exposure as additional co-reactant before or after the H2 plasma step also plays a role in the nucleation density and particle coalescence, affecting also the shape of the deposited particles. Based on the gathered knowledge, a synthetic approach that enables precise control of the Pd nanoparticle dimensions and coverage is developed.